CONTROL OF THE CFTR CHANNEL’S GATES - Vergani, Paola (2005)
Unique among ABC (ATP-binding cassette) protein family members, CFTR (cystic fibrosis transmembrane conductance regulator), encoded by the gene mutated in cystic fibrosis patients, functions as an ion channel. Opening and closing of its anion-selective pore are linked to ATP binding and hydrolysis at CFTR’s two nucleotide binding domains, NBD1 and NBD2. Isolated NBDs of prokaryotic ABC proteins form homodimers upon binding ATP, but separate after hydrolysis of the ATP. By combining mutagenesis with single-channel recording, nucleotide photolabeling, and sulfhydryl-specific crosslinking methods on intact CFTR molecules, we relate opening and closing of the channel gates to ATP-mediated events in the NBDs. In particular, we demonstrate that two CFTR residues, predicted to lie on opposite sides of its anticipated NBD1-NBD2 heterodimer interface, are energetically coupled when the channels open but are independent of each other in closed channels. This directly links ATP-driven tight dimerization of CFTR’s cytoplasmic nucleotide binding domains to opening of the ion channel in the transmembrane domains. Evolutionary conservation of the energetically coupled residues in a manner that preserves their ability to form a hydrogen bond argues that this molecular mechanism, involving dynamic restructuring of the NBD dimer interface, is shared by all members of the ABC protein superfamily.